Preliminary checklist of millipedes, worms and freshwater molluscs within the Marai Parai area of Kinabalu Park - Ting Hui Ng (Sabah Parks Nature Journal, 2024)
Borneo is known as a biodiversity hotspot but many less-charismatic, yet ecologicallyimportant invertebrate species remained largely neglected. This study aims to record the diversity and distribution of millipede, worm (annelid and flatworm) and freshwater mollusc species within the Marai Parai area of Kinabalu Park. The terrestrial fauna (i.e., myriapods and worms) were surveyed in the day and night along the trails, while freshwater molluscs were collected by hand in shallow water bodies. Millipedes from three orders were collected, potentially consisting of eight species. Among the annelid worms, the earthworms may potentially consist of two species, while the leeches, which included terrestrial and aquatic species, may potentially consist of 4–5 species. For flatworms, three species were recorded. Only one species of freshwater mollusc, Melanoides tuberculata, was recorded from the paddy fields of Kampung Kiau Nuluh. Aside from the mollusc, the other taxa, i.e., millipedes, annelids and flatworms, all require further research to clarify their identities, with the possibility of new species being discovered.